PRINCIPLES OF THE KARAKALPAK LANGUAGE ORTHOGRAPHY - Dlanova Palzira Gulimbetovna (Bright Mind Publishing, 2025)
This article discusses the formation and improvement of orthographic skills for students studying in higher education institutions to understand the phonetic and grammatical features of the language, the peculiarity of spelling and its special importance to help students to fully and firmly master the Karakalpak language. After graduating from a secondary school in a foreign language, students must be able to learn the basic rules of the Karakalpak language, be able to communicate their texts orally and in writing. It is also important to know spelling.
Keywords: Spelling, morphology, phonetics, text, princip, oral, written.